2007
DOI: 10.1103/physrevb.75.174109
|View full text |Cite
|
Sign up to set email alerts
|

Resolution-function theory in piezoresponse force microscopy: Wall imaging, spectroscopy, and lateral resolution

Abstract: Oak Ridge, TN 37831 Piezoresponse Force M icroscopy (PFM ) has emerged as a primary tool for imaging, domain engineering, and switching spectroscopy on ferroelectric materials. Quantitative interpretation of PFM data including measurements of the intrinsic width of the domain walls, geometric parameters of the domain below the tip in local hysteresis loop measurements, as * Permanent address: V.Lashkaryov Institute of Semiconductor Physics, National Academy of Science of Ukraine, 41, pr. Nauki, 03028 Kiev, Ukr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
116
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(127 citation statements)
references
References 45 publications
10
116
0
1
Order By: Relevance
“…Figure 2 shows the calculated line scans for LiNbO 3 from Ref. [15] in comparison with our experimental results obtained with a diamond coated tip of radius r = 60 nm (confirmed by scanning electron microscopy). Neither the amplitudes nor the shapes are well reproduced by the theoretical calculations.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Figure 2 shows the calculated line scans for LiNbO 3 from Ref. [15] in comparison with our experimental results obtained with a diamond coated tip of radius r = 60 nm (confirmed by scanning electron microscopy). Neither the amplitudes nor the shapes are well reproduced by the theoretical calculations.…”
mentioning
confidence: 93%
“…15 In this work, the displacement of the sample surface underneath the tip is calculated, especially for scanning across 180 • domain boundaries. Here the tip is assumed to follow this displacement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…86 The reason for the faster response saturation is that the tip potential quickly vanishes for small R d leading to a strong decrease of the PFM response region ͑R max , h max ͒. The space outside the region ͑R max , h max ͒ is invisible to PFM, so when the domain radius reaches R max and height acquires h max , respectively, the response almost saturates.…”
Section: B Piezoresponse In the Intermediate Statesmentioning
confidence: 99%
“…However, subsequent studies have questioned these scenarios after quantifying the resulting lateral force, and suggested instead the possibility of electrostatic effects arising from the electric field present around domain walls due to the buildup of opposite surface polarization charges. 14 Concurrently, numerical analyses in the framework of resolution-function theory showed that in a c-axis tetragonal film, local shear can occur at the domain wall, 15 potentially giving rise to a lateral PFM signal. Discriminating between these different contributions to identify the mechanism at the origin of the observed signal is all the more necessary as PFM becomes widely applied to more complex materials such as BiFeO 3 ͑BFO͒, presenting both in-plane and out-of-plane polarization components, and where all possible contributions to both vertical and lateral PFM signals have to be taken into account.…”
mentioning
confidence: 99%